1990
DOI: 10.1007/bf02055545
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of small flat carcinoma of the colon

Abstract: Most small carcinomas arise from polyps. Small lesions with cellular features of malignancy and early invasion, but with no histologic evidence of residual adenoma, are rare. Diagnosed by endoscopy, three such lesions are described. They were recognized as mucosal plaques, measuring between 6 and 8 mm in diameter. In each case, there was either synchronous or metachronous carcinoma elsewhere in the colon, as well as benign adenomatous polyps. Colonoscopic identification of such lesions allows inclusion of that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Recently, however, several reports from the western world have found that small colorectal carcinomas can be detected at a similar frequency when endoscopic techniques such as those used in Japan are employed [5,18,37,42,43,44]. In 1995, our group published a series in Germany describing 155 de novo carcinomas collected between 1988 and 1994 that were no more than 1.0 cm in diameter [45].…”
Section: Controversy In the Westmentioning
confidence: 96%
“…Recently, however, several reports from the western world have found that small colorectal carcinomas can be detected at a similar frequency when endoscopic techniques such as those used in Japan are employed [5,18,37,42,43,44]. In 1995, our group published a series in Germany describing 155 de novo carcinomas collected between 1988 and 1994 that were no more than 1.0 cm in diameter [45].…”
Section: Controversy In the Westmentioning
confidence: 96%
“…(11) Presence or absence of perineural invasion. (12) Presence or absence of lymph node metastases. (13) Presence or absence, and grade, of dysplasia (low or high) of adjacent adenomatous epithelium, where present, as per previously published criteria.…”
Section: Pathologic Analysismentioning
confidence: 99%
“…2,3,14,39,40 Some investigators believe that de novo carcinomas arise directly from normal mucosa and develop via a distinct pathway of carcinogenesis with, possibly, a more aggressive phenotype. 2,11,27,40 These tumors have been described by a variety of names, such as ''superficial'' 11,46 (including flat, 12,25,40,42 depressed, 11,14,23 and ulcerated 20 ), ''early'' 14,25,27 (generally applied to carcinomas limited to the mucosa and/or submucosa), ''nonpolypoid,'' 3,19,22 and de novo 2,24,39 carcinomas.…”
mentioning
confidence: 99%
“…Whether depressed or not, rather few cases of non‐polypoid early colon cancers have been reported by Western researchers. 17–21 This is probably because candidate lesions are overlooked as a result of ignorance of and/or resistance to the concept or because proper diagnostic methods are not used. High‐magnification colonoscopy and chromoscopy clearly improve the detection rate of non‐polypoid neoplastic lesions.…”
Section: Detection Of Flat Adenomas and Depressed Lesionsmentioning
confidence: 99%